2015
DOI: 10.1016/j.celrep.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

MLL-Rearranged Acute Lymphoblastic Leukemias Activate BCL-2 through H3K79 Methylation and Are Sensitive to the BCL-2-Specific Antagonist ABT-199

Abstract: SummaryTargeted therapies designed to exploit specific molecular pathways in aggressive cancers are an exciting area of current research. Mixed Lineage Leukemia (MLL) mutations such as the t(4;11) translocation cause aggressive leukemias that are refractory to conventional treatment. The t(4;11) translocation produces an MLL/AF4 fusion protein that activates key target genes through both epigenetic and transcriptional elongation mechanisms. In this study, we show that t(4;11) patient cells express high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
132
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 45 publications
11
132
1
Order By: Relevance
“…In MLL-r ALL xenografts, venetoclax was associated with a higher response rate of 50%, compared with 26% in non-MLL-ALL xenografts, suggesting that BCL-2 inhibition, in conjunction with chemotherapeutics, is effective in this sub-group (93,94). These data support the trial of the introduction of BCL-2-inhibitor drugs into therapeutic regimens for MLL-r leukemias (84).…”
Section: Minireview: Leukemia Fusions and Apoptosissupporting
confidence: 70%
“…In MLL-r ALL xenografts, venetoclax was associated with a higher response rate of 50%, compared with 26% in non-MLL-ALL xenografts, suggesting that BCL-2 inhibition, in conjunction with chemotherapeutics, is effective in this sub-group (93,94). These data support the trial of the introduction of BCL-2-inhibitor drugs into therapeutic regimens for MLL-r leukemias (84).…”
Section: Minireview: Leukemia Fusions and Apoptosissupporting
confidence: 70%
“…This observation extends a recent published finding that MLL rearrangement directly induces BCL-2 expression in ALL cells by promoting H3K79 methylation at the BCL2 locus. 62 In that study, single-agent efficacy was observed in 1 of 2 MLLr-ALL xenografts treated with venetoclax in vivo. Notably, even within the MLLr-ALL subgroup, we found Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…BH3 profiling and studies using the LOUCY cell line indicate that venetoclax, alone or in combination with chemotherapeutic agents, may represent a powerful new therapeutic strategy for ETP T-ALL (117119). Benito and colleagues found that blasts from mixed lineage leukemia-rearranged (MLLr) ALL express high levels of BCL-2, and ChIP sequencing analysis demonstrated that the BCL2 gene is a direct MLL-AF4 target (120). MLL-AF4 maintains BCL2 gene expression through H3K79 methylation, which translates into high sensitivity of MLLr cell lines and primary cells to venetoclax, alone or in combination with standard induction chemotherapeutics or H3K79 methylation inhibitors.…”
Section: Future Considerations and Conclusionmentioning
confidence: 99%